Sialidase facilitates Porphyromonas gingivalis immune evasion by reducing M1 polarization, antigen presentation, and phagocytosis of infected macrophages - Fan, Xiaomiao; Zheng, Shaowen; Chen, Chen; Lin, Li; Wang, Hongyan; Shen, Yuqin; Pan, Yaping; Li, Chen (Frontiers in Cellular and Infection Microbiology, 2023)
Background Porphyromonas gingivalis (P. gingivalis), a major pathogen of periodontitis, can evade host immune defenses. Previously, we found that P. gingivalis W83 sialidase gene mutant strain (ΔPG0352) was more easily cleared by macrophages. The aims of this study were to investigate the effects of sialidase in P. gingivalis on the polarization, antigen presentation, and phagocytosis of infected macrophages and to clarify the mechanism of P. gingivalis immune evasion. Methods Human monocytes U937 were differentiated to macrophages and infected with P. gingivalis W83, ΔPG0352, comΔPG0352, and Escherichia coli (E. coli). The phagocytosis of macrophages was observed by transmission electron microscopy and flow cytometry. ELISA or Griess reaction were used to examine the levels of interleukin-12 (IL-12), inducible nitric oxide synthase (iNOS) and interleukin-10 (IL-10), and the expressions of CD68, CD80 and CD206 were determined by flow cytometry. The expression of major histocompatibility complex-II (MHC-II) was detected by immunofluorescence. A rat periodontitis model was established to determine the M1 and M2 polarization of macrophages. Results Compare with P. gingivalis W83, ΔPG0352 increased the levels of IL-12, iNOS, CD80, and MHC-II and inhibited the levels of IL-10 and CD206. Macrophages phagocytosed 75.4% of ΔPG0352 and 59.5% of P. gingivalis W83. In the rat periodontitis model, the levels of M1 and M2 macrophages in P. gingivalis W83 group were both higher than those in ΔPG0352 group, while the ratio of M1/M2 was higher in the ΔPG0352 group. Alveolar bone absorption was lower in ΔPG0352 group. Conclusion Sialidase facilitates P. gingivalis immune evasion by reducing M1 polarization, antigen presentation, and phagocytosis of infected macrophages.